Knowledge management system of coconut - Chin, Pooi Ling (2012)
Knowledge Management System Of Coconut (KMSOC) is Knowledge Management online System for Pahang State Agriculture Department. This system can guide and help users especially farmers through sharing knowledge and experience. Farmers or users who are hard to control pests and care of coconut crop without knowledge and experience. Farmers and users can not share their knowledge and experience Without this Knowledge Management online system. This KMSOC is online system can assist users to share their experiences to each other. Any knowledge and information that farmers share will save into database that is MySQL. To complete this system built, Waterfall Software Development Life cycles (SDLC) is used. This system development methodology has five phrases that are planning, analysis, design, implementation and maintenance. Target • users of this system are farmer, supplier, customer, expert, staff and admin. This is because KMSOC can let farmers share coconut knowledge based on their experience to users who are using this system. Suppliers can post their any Coconut products in Coconut Advertisement. As a result, It will help users especially farmers who will get knowledge from other people.